ANALISIS PERTANYAAN PADA BUKU TEKS IPA SMP KURIKULUM MERDEKA BERDASARKAN QUESTION CATEGORY SYSTEM FOR SCIENCE (QCSS) PADA KONSEP GERAK DAN GAYA - Afia, Kholifa Nur; Hodijah, Siti Romlah Noer; Rohimah, Rt. Bai (PendIPA Journal of Science Education, 2025)
This study aimed to analyze the classification and distribution of questions in two Grade VII science textbooks under the Merdeka Curriculum on the topic of motion and force, published by Kemendikbudristek (2021) and Erlangga. The research employed a qualitative method with a content analysis approach, focusing on categorizing questions based on the Question Category System for Science (QCSS), which distinguishes four levels of thinking skills: cognitive memory, convergent, divergent, and evaluative. The data consisted of 103 questions identified from both textbooks and were supported by preliminary interviews with junior high school science teachers. The findings indicate that both textbooks consistently place convergent thinking as the dominant category, with 70% in Kemendikbudristek and 71.83% in Erlangga. However, significant differences emerge in higher-order thinking skills: the Kemendikbudristek textbook emphasizes divergent questions (61.53%) that encourage creativity and idea exploration, while the Erlangga textbook prioritizes evaluative questions (77.77%) that strengthen critical reasoning and decision-making. These findings reveal different pedagogical orientations, with Kemendikbudristek focusing more on fostering creativity and exploration, while Erlangga emphasizes critical thinking skills. In conclusion, both textbooks are relevant in fostering convergent thinking skills, yet a balanced proportion of divergent and evaluative questions is needed to comprehensively support students’ critical, creative, and scientific thinking in accordance with the demands of 21st-century learning.